Counter-Terrorism Medicine: Creating a Medical Initiative Mandated by Escalating Asymmetric Attacks - Court, Michael; Edwards, Brydie; Issa, Fadi; Voskanyan, Amalia; Ciottone, Gregory (Prehospital and disaster medicine, 2020)
Introduction:Since 2001, a burgeoning interest by health care professionals in the growing asymmetrical terrorist threat and its impact on health care preparation and response has seen significantly increased academic output around this nebulous subject. Despite this, there has failed to be a consolidation of this sub-specialty.Discussion:This editorial argues for the consolidation of the body of experience gathered since 2001 into an initiative called Counter-Terrorism Medicine (CTM). It proposes that previously discrete sub-specialty areas can be consolidated, with improvements in collective understanding, and can build on previous work to provide a non-political health care focused definition of terrorist events, based on the triad of Violence, Intent, and Heath Care Impact. It notes the importance this defining triad has in health care planning and response considerations. Finally, it defines the parameters of CTM within the larger specialty of Disaster Medicine (DM).Conclusion:There is a growing body of academic work on the health care implications of terrorism. The time is right to coalesce these into an initiative referred to as CTM and to consider this as a discrete part of DM.